Biological Properties Of Monstera Deliciosa Using Zinc Nanoparticles - Poludasu, Prabhakar; Babu, K. Suresh (Frontiers in health informatics, 2025)
The tropical Monstera deliciosa is well-known for its aesthetic value as well as its bioactive and therapeutic qualities. The use of metal-based nanoparticles to increase medicinal plants' biological potential has recently become possible because to developments in nanotechnology. The antibacterial, antioxidant, and phytochemical qualities of Monstera deliciosa are the subject of this research, which investigates the effect of zinc nanoparticles (ZnNPs) on these biological traits. We used spectroscopic and microscopic techniques, such as UV-Vis spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and X-ray Diffraction (XRD), to determine the structural, morphological, and optical properties of the ZnNPs that were synthesized using both chemical and green methods.   By examining its development, biochemical make-up, and the improvement of its bioactive components, the relationship between ZnNPs and Monstera deliciosa was evaluated. Disk diffusion and minimum inhibitory concentration (MIC) tests were used to assess the antibacterial effectiveness against various bacterial and fungal strains, while assays including DPPH and ABTS radical scavenging were used to quantify the antioxidant activity of plant extracts treated with ZnNPs. The effects of ZnNP exposure on secondary metabolite synthesis were also investigated by phytochemical screening.   The findings showed that Monstera deliciosa's antioxidant capacity and antibacterial potential were greatly improved after treatment with ZnNPs, suggesting that ZnNPs may be used as bio stimulants to boost the therapeutic potential of plant-derived extracts. The addition of ZnNPs also affected the production of flavonoids and phenolic compounds, two classes of chemicals with well-documented powerful biological effects. Based on these results, it seems that ZnNPs may be a useful tool for improving medicinal plants' pharmacological effects and creating new nano pharmaceuticals derived from plants.   This work sheds fresh light on the use of metal nanoparticles to enhance the biological effectiveness of medicinal plants, which might lead to exciting new developments in the fields of plant sciences and herbal medicine. A novel strategy to bioengineering plant-based therapies is shown by the integration of ZnNPs with Monstera deliciosa. This technique might have important consequences for both the biomedical and agricultural sectors. For nanotechnology to be used safely and sustainably in botanical research, future studies should investigate how ZnNP exposure affects plant physiology over the long run and what consequences this may have on human health.